PERANCANGAN MEDIA PROMOSI LEMBAGA PENDIDIKAN ENGLISH LANGUANGE TRAINING INTERNASIONAL (ELTI) PADA PROGRAM ENGLISH FOR KINDERGARTEN MELALUI MEDIA PRINT AD DENGAN TEKNIK ILUSTRASI - Sapto Utomo (Canthing, 2012)
Designing Media Promotion Institutions English Languange Training Internasional (ELTI) In English For Kindergarten Program Through Print Media Ad with illustration techniques.Our country to Â realize that mastery of English is essential to face global competition. Emerged a new paradigm in which the parents have started to invest the knowledge their children to learn English from an early age. The design of this media campaign raised the issue of how to make the formulation of an effective media campaign through illustration techniques to image / image ELTI English for Kindergarten institutions could be created. The purpose of designing a media campaign is to determine the effectiveness of promotional media ELTI English for Kindergarten through illustration and image formation approach of the institute. Method of designing a media campaign is persuasife method, in which the design is not attractive in terms of promotion of the visual, but there is an element so that consumers may be interested pengajakan.The design of this media campaign was known that the effectiveness of the promotion of English for Kindergaten ELTI illustration of the technique is high, it is justified because the selection of the line bellows media devastating directly to consumers.